Integrasi Pasar Saham Indonesia Dengan Pasar Saham Asia - Didik Gunawan; Willy Cahyadi (Jurnal Pasar Modal dan Bisnis, 2019)
This study aims to prove the integration of the Indonesian stock market with the stock markets of countries in Asia, especially the largest trading partners. The population in this study is the monthly data of Nikkei225, KLSE, STI, SSE and LQ45 for the period 2014 to 2018, using VAR modeling. The results of this study prove that in the interaction of the Indonesian stock market with Asian trading partners, especially China, Japan, Singapore and Malaysia, this study proves that only Japan is not significantly related to the Indonesian economy, the decline in trade volume and trade wars are the main causes of these results.